DEVELOPMENT AND EVALUATION OF AN INFORMATION BULLETIN FROM THE NATIONAL DRUG INFORMATION CENTER OF COSTA RICA FOR HEALTH PROFESSIONALS AND STUDENTS - Tovar-Arrieta, Roberto (2026)
Objective: To develop a bulletin from the National Drug Information Center (CIMED®) of Costa Rica that complies with the accreditation standards of the International Society of Drug Bulletins, thereby enhancing access to reliable updated health-related information for healthcare professionals and students in Costa Rica. Method: The bulletin was desing based on a needs assessment conducted through surveys, along with benchmarking analysis of bulletins accredited by the International Society of Drug Bulletins. Results: Two initial editions were designed on topics of interest—Parkinson’s disease and oncology patients—and published in the Kérwá repository of the University of Costa Rica. The evaluation revealed high levels acceptance regarding design, content, and format. Conclusion: The bulletin represents a key tool for strengthening academic training, clinical practice, and scientific dissemination, consolidating CIMED® as a reference center in pharmaceutical and health information.